REPUTATIONAL AND OPERATIONAL RISKS IN EUROPEAN BANKS - Roxana HERGHILIGIU (SEA: Practical Application of Science, 2014)

(untitled)
In the past 20 years operational and reputational risk has become more intriguing due to the public scandals of rogue tranding in banks like Barings Bank, Allied Irish Banks, Enron. The purpose of this study is to find the connections between operational risk and reputational risk. Our research shows that there may be a loss of reputation due to operational loss events. Moreover, every type of operational risk, from internal fraud, external fraud, legal and liability losses, processing errors, information security breaches, inappropriate business practice, physical security breaches conduct to a loss of reputation. The limitations of this paper are represented by the fact that do not have enough data to show the real impact of the reputation risk to the financial results of the European Banks.